Traffic safety evaluation using surrogate safety measures in the context of Indian mixed traffic: A critical review - N. Mohamed Hasain; Mokaddes Ali Ahmed (IATSS Research)
The concern over road safety has increased in the last several decades, especially in developing countries like India. Even with increasing road accidents, crash data at a particular location is mostly underreported. Hence, using the Traffic Conflict Technique (TCT) with Surrogate Safety Measures (SSMs) to evaluate traffic safety instead of accident data has gained significant attention among researchers in India. However, the traffic existing in the country is more complex and diverse than most of the developed nations around the world. This led the researchers to modify the existing methods and propose new methods to address the heterogeneity of the existing mixed traffic. The current study formulated six research questions to guide the review process. Since the number of studies in the area of research is increasing rapidly, there is a need to study the current state of the art in the country. Hence, the paper critically reviewed thirty-three studies conducted in the area of research in Indian conditions, including their findings and limitations. Further, an overview of sixteen commonly used SSMs worldwide was presented, along with some potential research gaps and recommendations.